Космические технологии на рубеже веков: итоги и перспективы - Семенов, Ю.П. (Автоматическая сварка, 2003)
Представлены основные научно-технические достижения РКК "Энергия" им. С. П. Королева за последнее десятилетие как иллюстрация успехов ракетно-космической отрасли на международном рынке передовых наукоемких технологий в интересах освоения космического пространства в ХХI веке. Эти достижения были бы немыслимы без решения многообразных проблем сварки вместе с ведущей организацией в этой области - ИЭС им. Е. О. Патона. The paper presents the main scientific-technical achievements of S.P. Korolyev RSC "Energia" over the last decade as aillustration of the successes of the rocket-space industry in the international market of advanced science-intensive technologies for space mastering in the XXIst century. These achievements would be unthinkable without solving the diverse problems of welding to together with the leading organization in this field - the E.O. Paton Electric Welding Institute.